IL-8 and LYPD8 expression levels are associated with the inflammatory response in the colon of patients with ulcerative colitis - Okada, Tomoyuki (Biomed Rep, 2020)
Ulcerative colitis (UC) is an idiopathic chronic inflammatory disorder affecting the large intestine, which may involve mucosal degeneration. Glycoproteins, mucin2 (MUC2) and the LY6/PLAUR domain containing 8 (LYPD8) are present on the mucous layer of the colon and can hinder the invasion of bacteria, thus contributing to the prevention of colitis. The present study investigated the expression levels of interleukin-8 (IL-8), MUC2 and LYPD8 on the mucous membranes of patients with UC. A total of 18 patients with UC (6 females and 12 males) were examined. Biopsies of the lesions as well as matching normal membranes were obtained and the mRNA expression levels of IL-8, MUC2 and LYPD8 were compared. LYPD8 expression was downregulated in the lesions and the relapsing-remitting subtype of lesions was associated with higher levels of MUC2 expression compared with single attack and chronic lesions subtypes. A positive correlation between Matts' histopathological grade and IL-8, as well as a negative correlation between Matts' histopathological grade and LYPD8 were observed. The expression levels of LYPD8 were lower in highly active lesions and these levels decreased according to the intensity of the mucosal inflammation. Conversely, an increase in MUC2 expression levels may reflect the recovery of the outer mucus layer in the remission phase. Therefore, the examination of MUC2 and LYPD8 expression levels may be useful indicators of mucosal healing in patients with UC.